Managing voltage fluctuation issues in distribution system connected with distributed generation using decentralized power factor control - Tengku Juhana Tengku Hashim,; Nofri Yenita Dahalan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Power quality issues has evidently become one of the crucial issues in power system studies. With the integration of distributed generations (DGs) in the power system, the issue of voltage control has become very important as the power system has become dynamic due to the bidirectional power flow. Delivering power while maintaining acceptable voltage limits has become very challenging for the distribution network operators (DNOs). In order to maintain power delivery to the customers whilst maintaining good power quality, the DNOs has undertaken several measures including implementing several voltage control methods to guarantee that the voltage limits in the power system are within permissible limits. This includes the centralized and decentralized voltage control techniques in the system connected with DGs. The DGs are connected to buses 9 and 14 of the test system where these two buses have been identified as the weakest bus. The decentralized voltage control method has also become an acceptable option due to its ease in having limited communication and lower costs in the system. One of the decentralized voltage control method which has been widely used is the power factor control (PFC) method. The IEEE 14 bus distribution test system has been used and integrated with DGs to show the effectiveness of the PFC method in managing the voltage fluctuation issues in the distribution system.